2022
DOI: 10.1038/s42003-022-03506-6
|View full text |Cite
|
Sign up to set email alerts
|

GPR87 promotes tumor cell invasion and mediates the immunogenomic landscape of lung adenocarcinoma

Abstract: The purpose of this study is to examine the association between G protein-coupled receptor 87 (GPR87) and lung adenocarcinoma (LUAD) metastasis and immune infiltration. The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets extract clinical data. According to the TCGA database, increased GPR87 expression predicts poor overall survival, progression-free interval, and disease-specific survival in LUAD patients. The meta-analysis also reveals a significant association between high GPR87 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…According to the ceRNA hypothesis [28], lncRNAs in the lncRNA-hsa-miR-1-3p -TIMELESS interaction network in LUAD should be oncogenic. Expression, survival and correlation analyses identified MIR4435−2HG as a candidate oncogenic lncRNA in the lncRNA-hsa-miR-1-3p -TIMELESS Research has revealed that some genes including circadian genes can alter tumor immune cell infiltration and influence prognosis [12,[33][34][35]. The present study adds to this evidence-…”
Section: Plos Onesupporting
confidence: 54%
See 1 more Smart Citation
“…According to the ceRNA hypothesis [28], lncRNAs in the lncRNA-hsa-miR-1-3p -TIMELESS interaction network in LUAD should be oncogenic. Expression, survival and correlation analyses identified MIR4435−2HG as a candidate oncogenic lncRNA in the lncRNA-hsa-miR-1-3p -TIMELESS Research has revealed that some genes including circadian genes can alter tumor immune cell infiltration and influence prognosis [12,[33][34][35]. The present study adds to this evidence-…”
Section: Plos Onesupporting
confidence: 54%
“…Research has revealed that some genes including circadian genes can alter tumor immune cell infiltration and influence prognosis [ 12 , 33 35 ]. The present study adds to this evidence-base.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis of the microarray dataset GSE72094 has uncovered a perplexing discrepancy that challenges the prevailing understanding of LGR4's role in LUAD prognosis. Few studies have focused on the prognostic value of LGR4, while the majority of these studies and analyses [27][28][29][30], including our own TCGA analysis, have consistently associated higher expression levels of LGR4 with worse OS in LUAD patients, our validation results based on the microarray dataset revealed a strikingly contrasting pattern. Surprisingly, we observed that lower expression levels of LGR were correlated with poor OS, in direct opposition to the established consensus.…”
Section: Discussionmentioning
confidence: 81%
“…Our analysis of the microarray dataset GSE72094 has uncovered a perplexing discrepancy that challenges the prevailing understanding of LGR4 role in LUAD prognosis. Few studies have focused on the prognostic value of LGR4, while the majority of these studies and analyses, [48–51] including our own TCGA analysis, have consistently associated higher expression levels of LGR4 with worse OS in LUAD patients, our validation results based on the microarray dataset revealed a strikingly contrasting pattern. Surprisingly, we observed that lower expression levels of LGR were correlated with poor OS, in direct opposition to the established consensus.…”
Section: Discussionmentioning
confidence: 85%